Effects of feeding level and C/N ratio on water quality, growth performance, immune and antioxidant status of Litopenaeus vannamei in zero –water exchange bioflocs-based outdoor soil culture ponds. Issue 101 (June 2020) - Tong, Ruixue; Chen, Wenbin; Pan, Luqing; Zhang, Kaiquan
Abstract: Two trials were conducted as follows: the first trial was a 90-day experiment to determine the effects of reducing feeding level on shrimp status; the second trial (90 days) is based on the first trial to explore the suitable C/N ratio of biological flocs for shrimp culture in outdoor soil ponds. Results showed that the BFV levels increased gradually and then tended to be stable in the treatment groups. Concentrations of TAN and NO2 –N were maintained low level in each treatment pond during experimental period. The final body weight, biology body length and yield of the shrimp in each trial with no significantly different ( P > 0.05) while food coefficient and THC of the shrimp in 70% feeding level and C/N12 treatment were slightly lower than in the 100% feeding level and C/N16 treatment respectively ( p < 0.05). The antibacterial activity and bacteriolytic activity in C/N16 treatment group were higher than in C/N12 ( p < 0.05), while there were no significant difference between the two feeding levels (70%, 100%) ( P > 0.05). The shrimp in 70% feeding level and C/N12 treatment had the higher T-AOC in both the plasma and the hepatopancreas when compared with 100% feeding level and C/N16 treatment group ( p < 0.05). The SOD activity of plasma in 70% treatment group was higher than in 100% ( p < 0.05), while it was no significant difference between the two C/N ratios (12, 16) in both the plasma and the hepatopancreas ( P > 0.05). The effects of two feeding levels and C/N ratios on the GSH level and the ratio of GSH/GSSG in the plasma and the hepatopancreas of shrimp showed no significant difference ( P > 0.05). The results showed that 70% feeding level and C/N12 ratio could provide adequate nutrition for shrimp to maintain a normal physical health status with the presence of bioflocs. Highlights: Bioflocs helped to maintain good water quality in outdoor soil pond culture. Feeding level reduced from 100% to 70%, didn't affect the survival and growth of shrimp. The growth and physiological health of shrimp were not significantly affected when C/N ratio at 12. Feeding level at 70% and C/N ratio at 12 decreased food coefficients without affecting yield of shrimp. A new model of shrimp culture in the bioflocs system of outdoor earth pond was established.